2014
DOI: 10.1016/j.enbuild.2014.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Energy performance comparison of three innovative HVAC systems for renovation through dynamic simulation

Abstract: Energy performance comparison of three innovative HVAC systems for renovation through dynamic simulation. Buildings, http://dx.doi.org/10. 1016/j.enbuild.2014.07.059 Access to the published version may require subscription. N.B. When citing this work, cite the original published paper. Energy and Permanent link to this version:http://urn.kb.se/resolve?urn=urn:nbn:se:du-15163 Energy and Buildings 82 (2014) a b s t r a c tIn this paper, dynamic simulation was used to compare the energy performance of three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(16 citation statements)
references
References 5 publications
(5 reference statements)
1
11
0
2
Order By: Relevance
“…In addition, above 70% of building energy in Germany is consumed by the space heating (Wang, 2015). Similar statistical results occur in the major of other countries, where around 40% of total annual energy has been consumed in buildings (Gustafsson et al, 2014; Liu et al, 2010). Demand controlled ventilation (DCV) could be used to reduce heating consumption while maintaining an acceptable indoor environment (Jia et al, 2016).…”
Section: Introductionsupporting
confidence: 82%
“…In addition, above 70% of building energy in Germany is consumed by the space heating (Wang, 2015). Similar statistical results occur in the major of other countries, where around 40% of total annual energy has been consumed in buildings (Gustafsson et al, 2014; Liu et al, 2010). Demand controlled ventilation (DCV) could be used to reduce heating consumption while maintaining an acceptable indoor environment (Jia et al, 2016).…”
Section: Introductionsupporting
confidence: 82%
“…The conversion of radiators to ventilation radiators implies installing air ducts through the wall behind them. The radiators will then preheat supply air and enable a lower water temperature in the heating system [22,39]. In C2, 7 of the 14 radiators in each zone were converted to ventilation radiators, giving an air flow of 8.9 l/s per ventilation radiator.…”
Section: Building and System Modelsmentioning
confidence: 99%
“…As a result, the district heating temperature will also be better suited for low-temperature heating systems, such as floor heating or low-temperature radiators, with distribution temperatures of 35 -45 °C [21]. Previous studies by Gustafsson et al [22,23] have shown that exhaust air heat pump (EAHP) and mechanical ventilation with heat recovery (MVHR) can both be beneficial solutions, with respect to cost and energy consumption, for energy renovation of single family houses in northern and central Europe, and that the advantage of heat recovery from exhaust air becomes larger in cold climates. Furthermore, these studies showed that low-temperature radiator systems improve the energy performance of heat pumps.…”
Section: Introductionmentioning
confidence: 99%
“…Nagrinėto pastato vėsinimo sistemos ekserginis efektyvumas dar žemesnis -6,81 %. Gustafsson et al (2014) taikydami net kelias modeliavimo priemones -Matlab Simulink ir TRNSYS -tiria tipišką šiaurės vakarų Europos gyvenamąjį namą. Modeliuojamos kelios to paties namo šildymo sistemos, naudojančios šilumos siurblį.…”
Section: įVadasunclassified